The Effect of Group Guidance Using Group Exercise Techniques on the Career Selection Ability of High School Students - Basyarah, Siti Farida; Marjo, Happy Karlina; Herdi, Herdi (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2021)
The purpose of the study was to describe the profile of the career selection ability of students in the science department of SMA Negeri 7 Bekasi before and after group guidance services were carried out with group exercise techniques and the effect of group guidance with group exercise techniques on the career selection abilities of students in science majors at SMAN 7 Bekasi City. The research method used is an experimental design with a nonequivalent (pretest-posttest) control group design. The population is 180 students and the sample is 40 students taken by random sampling. The data collection technique is a questionnaire with a Likert scale. The data analysis technique used is the Independent Samples Test. The results showed that there was a significant effect of providing group guidance with group exercise techniques on the career selection skills of students majoring in science at SMAN 7 Bekasi City.Keywords: group guidance; group exercise techniques; career selection skillsTujuan penelitian untuk mendeskripsikan profil kemampuan pemilihan karier siswa Jurusan IPA SMA Negeri 7 Bekasi sebelum dan sesudah dilakukan layanan bimbingan kelompok dengan teknik group exercise dan pengaruh bimbingan kelompok dengan teknik group exercise terhadap kemampuan pemilihan karier siswa jurusan IPA SMAN 7 Kota Bekasi. Metode penelitian yang digunakan adalah eksperimen dengan desain nonequivalent (pretest-posttest) control group design. Populasi berjumlah 180 siswa dan sampel berjumlah 40 siswa yang diambil dengan random sampling. Teknik pengumpulan data adalah angket dengan skala Likert. Teknik analisis data yang digunakan adalah dengan Independent Samples Test. Hasil penelitian menunjukkan terdapat pengaruh yang signifikan pemberian bimbingan kelompok dengan teknik group exercise terhadap kemampuan pemilihan karier siswa jurusan IPA SMAN  7 Kota Bekasi.Kata  Kunci:  bimbingan kelompok; teknik group exercise; kemampuan pemilihan karier